Clinical Effectiveness of Conservative Treatments on Lumbar Spinal Stenosis: A Network Meta-Analysis - Chen, Xuanwei; Zheng, Zhizhan; Lin, Jianhua (Frontiers in Pharmacology, 2022)
Objective: To systematically evaluate the clinical effectiveness of conservative treatments including pharmacological treatments and nonpharmacological treatments on patients with lumbar spinal stenosis. Methods: We searched six electronic databases systematically for randomized clinical trials published between January 2000 and July 2021, including the China National Knowledge Infrastructure, WanFang Data, PubMed, MEDLINE, Embase, and the Cochrane library. The studies focused on the therapeutic effects of pharmacological treatments including calcitonin, antiepileptics, neurotrophic drugs, nonsteroidal anti-inflammatory drugs, Chinese Traditional Medicine, limaprost, and nonpharmacological treatments like physiotherapy for treating lumbar spinal stenosis were included. The outcome was measured using the visual analog scale, Oswestry Dysfunction Index, Japanese Orthopaedic Association Score, and EuroQol Five Dimensions Questionnaire. The quality of eligible studies was assessed by using the Cochrane recommended bias risk assessment tool. Stata was used to conduct the network meta-analysis. Results: A total of 12 randomized control trials with 1,194 patients were included. The network meta-analysis showed that for the visual analog scale, a better therapeutic effect was noted while using Chinese Traditional Medicine and physiotherapy, followed by analgesics drugs and limaprost. Limaprost and calcitonin were better in decreasing the Oswestry Dysfunction Index. In terms of the Japanese Orthopaedic Association Score, the use of traditional Chinese Medicine and limaprost were associated with a better improvement than other treatments. Meanwhile, limaprost combined with analgesics drugs was found to be effective to improve the EuroQol Five Dimensions Questionnaire. Conclusion: Among the commonly used conservative treatments for the treatment of lumbar spinal stenosis, limaprost may have better efficacy in improving the Japanese Orthopaedic Association Score and decreasing the Oswestry Dysfunction Index, with a beneficial effect on decreasing the visual analog scale and improving the EuroQol Five Dimensions Questionnaire. Systematic Review Registration: website, identifier registration number.